Cinética pressórica e biodisponibilidade do óxido nítrico após o fracionamento de exercício concorrente em mulheres hipertensas - Azevêdo, Luan Morais (2016)
Physical exercise acts positively against the related risk factors for systemic arterial hypertension, a chronic and non-communicable disease that affects, approximately, 30% of the world population. Even though there are numerous studies that investigated the physiological responses of the exercise in this population, studying the "dose response" of its fractionation throughout the day becomes necessary, allowing new prescription possibilities. Therefore, this study aimed to evaluate ambulatory blood pressure kinetics after a fractionation of concurrent exercise session, as well as the nitric oxide bioavailability in hypertensive middle-aged women. In this way, eleven hypertensive middle-aged women (57.45 ±5.13 years) voluntarily participated of this study and underwent three experimental sessions and one control day (CS). In the morning (MS) and night (NS) sessions, the exercise was fully paid up in the morning and evening, respectively. In fractionized session (FS), it held 50% of the volume in the morning and the remaining 50% on the night shift. It was found that the MS provided greater decay and lower blood pressure reactivity (p<0.05) for systolic blood pressure (SBP) and diastolic blood pressure (DBP) 1h post-exercise, when compared to CS. The MS was also more effective in post-exercise hypotension for SBP than NS and FS, and promoted greater attenuation to pressure reactivity (p<0.05) than the other sessions. By analyzing the ambulatory blood pressure kinetic following the exercise, it was shown that the FS promoted lowest area under the blood pressure curve (p<0.05) for the SBP, DBP and MAP during sleep, as well as greater nitric oxide bioavailability (p<0.05) than the other sessions. In this sense, it is concluded that the FS was more effective in lower BP values at 24 hours following the exercise that other sessions, although this reduction has not been observed acutely, as observed after MS.